From 'Nazi cows' to cosmopolitan 'ecological engineers': specifying rewilding through a history of Heck cattle - Lorimer, J; Driessen, C (Routledge, 2015)
Rewilding has become a hot topic in nature conservation. Ambitious schemes are afoot to rewild continental Europe and North America. Hopes are being invested in the political, economic and therapeutic potentials of future wilds. However, popular and scientific enthusiasms for the wild are frequently ahistorical and apolitical. This article begins to address this problem. It offers one genealogy of rewilding, focusing on a history of Heck cattle and their deployment in European rewilding projects. These animals were back-bred by two German zoologists in the 1930s, with Nazi patronage, for release as hunting prey in the annexed territories of Eastern Europe. Some cattle survived the war and their offspring have become prominent, alongside new back-breeding initiatives, in contemporary efforts to rewild a unifying Europe. Cattle now figure as cosmopolitan ecological engineers, whose grazing will create functional, wild landscapes. This genealogy examines what and where is understood to be wild, and who is authorised to make such decisions in this story. Drawing cautiously on this extreme example, it examines historic rewilding as a form of reactionary modernism. It critically traces the emergence, persistence and transformation of various ontologies, geographies and epistemologies of wildness in Europe to position contemporary rewilding as a mode of ecomodernism. When compared, rewilding under Nazi rule and in the contemporary European Union are found to be different in every relevant problematic respect. Reflecting on differing conceptions of what it means to be modern, helps specify a multiplicity of rewildings past and present. The article concludes with a set of criteria for discriminating amongst rewildings to inform the emergence and analysis of this conservation paradigm.